Experimental investigation and thermo-economic performance analysis of a modified solar distiller design with thermal storage material and v-corrugated absorber basin. (25th August 2022) - Hammad, Farid A.; Shalaby, S.M.; Kabeel, A.E.; Zayed, Mohamed E.
Abstract: A comparative experimental study is carried out to augment the freshwater productivity of a single-slope solar distiller. A v-corrugated basin is utilized to boost the evaporation area for effective heat transfer of saline water; meanwhile, a phase change material (PCM) is incorporated underneath the basin to extend the still's nocturnal distillate yield. Paraffin wax is utilized as a PCM, and longitudinal copper fins are embedded inside the paraffin container to improve the heat transfer processes of the wax. Besides, the proposed solar distillers are investigated under flat and v-corrugated basin configurations with and without PCM. Four distillers, namely; traditional flat basin solar distiller (TFBSD), flat basin solar distiller with rearward copper longitudinal fins immersed in the PCM container (FBSD-PCM&Fins), v-corrugated basin solar distiller without PCM (VBSD), and v-corrugated basin solar distiller integrated with PCM (VBSD-PCM) are tested at the climatic conditions of Tanta (30.47° N and 31° E), Egypt. A comparative thermo-economic analysis of the four solar distillers is also performed, including the daily energetic efficiency, freshwater production, and distillate yield cost. The present results indicate that the VBSD-PCM maximized both energo-economic performance and freshwater production among the investigated modifications. The accumulated water production and the daily energetic efficiency of the VBSD-PCM are improved by 63.57 % and 72.70 %, respectively, compared to the TFBSD. Furthermore, the economic assessment shows that the cost of freshwater production of the VBSD-PCM is reduced by 23.10 % compared to the TFBSD. Highlights: A novel modifications of a single slope solar distiller were experimentally studied Two types of basin absorber configurations were comparatively studied with and without PCM V-corrugated basin integrated with PCM storage bed outperformed the investigated modifications Maximum yield enhancement was 63.57% for modified distiller over reference case Improvement in energy efficiency reached 72.70% for modified distiller over conventional one